The investigation of the water mist suppression pool fire process's flame expansion characteristics. (February 2023) - Liu, Yang; Chen, Peng; Fu, Zhixi; Li, Jiayan; Sun, Ruibang; Zhai, Xu
Abstract: Flame expansion is a typical fire suppression phenomenon that happens during the water mist suppression of liquid fuel fires, particularly heavy oil fires, and poses a risk to process safety. A series of transformer oil fire expansion experiments were carried out to study the mechanism of flame expansion in the process of water mist suppression pool fires. A theoretical model of the interaction of water mist with flame and hot fuel was developed after a quantitative investigation of flame structure changes during expansion. According to the results of the study, the presence of a fuel-rich vapor layer on the oil pool's surface is a prerequisite for flame intensification, and the thickness of this layer is proportional to the height of the transformer oil flame, L c = 0.195 L f . Furthermore, the impact of water mist on the fuel-rich vapor layer is found to be the principal cause of flame expansion, and the transformer oil flame expansion rate is determined using a combination of theoretical and experimental methods, φ v = 13.9 − 41.8 . Finally, one of the factors that aggravates flame expansion is the overpressure on the fuel surface caused by the water-oil mixture. Droplet size reduces as water mist pressure rises, and flame expansion shifts from the parallel effect of jet impact and water-oil mixing to the serial effect, lowering the flame expansion rate. As a result, reducing droplet size causes flame expansion to weaken. Highlights: Fuel-rich vapor layer thickness is inversely correlated with flame height and is necessary for flame intensification. L c = 0 . 195 L f . This research proposed a method for calculating flame expansion and the expansion rate of a transformer oil fire., φ v = 13.9 − 41.8 . The interaction of water mist with the oil pool's fuel-rich vapor layer is the primary cause of flame expansion. The reduction of droplet size aids in the reduction of flame expansion.